Management of bipolar II disorder - Michael M.C Wong (Indian Journal of Psychological Medicine, 2011)
Bipolar II disorder (BP II) disorder was recognized as a distinct subtype in the DSM-IV classification. DSM-IV criteria for BP II require the presence or history of one or more major depressive episode, plus at least one hypomanic episode, which, by definition, must last for at least 4 days. Various studies found distinct patterns of symptoms and familial inheritance for BP II disorder. BP II is commonly underdiagnosed or misdiagnosed. Making an early and accurate diagnosis of BP II is utmost importance in the management of BP II disorder. The clinician should have this diagnosis in mind when he is facing a patient presenting with mood problems, particularly unipolar depression. Quetiapine and lamotrigine are the only agents with demonstrated efficacy in double-blind RCT. Although the evidence for the use of lithium in long-term therapy is largely based on observational studies, the many years of close follow-up, comparatively larger subject numbers, and ′harder′ clinically meaningful with bipolar disorder outcomes measures, enhance our confidence in its role in treating BP II. With respect to short-term treatment, there is some limited support for the use of risperidone and olanzepine in hypomania and for fluoxetine, venlafaxine and valproate in treating depression. The current clinical debate over whether one should use antidepressants as monotherapy or in combination with a mood stabilizer when treating BP II depression is not yet settled. There is a need for large, well-designed RCTs to cast more definitive light on how best to manage patients with BP II disorder.